1999
DOI: 10.1038/sj.bmt.1702071
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy with hematopoietic stem cell transplantation in adults with bone marrow relapse of medulloblastoma: report of two cases

Abstract: Summary:Extraneural relapses of medulloblastoma are associated with a very poor outcome. We present two cases of young adults who developed bone marrow metastases after treatment of medulloblastoma. A very good response to a sequentially scheduled combination of carboplatin and etoposide was observed. Then, high-dose chemotherapy was delivered consisting of busulfan and thiotepa followed by infusion of autologous hematopoietic stem cells. Toxicity of the conditioning regimen was acceptable. The patients remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…14,[20][21][22] One case report of two patients has shown that high-dose chemotherapy consisting of busulfan and thiotepa followed by infusion of autologous hematopoietic stem cells produced disease-free survival times of 20 and 27 months after bone marrow relapse of medulloblastoma. 15 High-dose carboplatin, thiotepa and etoposide with autologous stem-cell rescue have also shown some activity against recurrent medulloblastoma. 11 High-dose chemotherapy is still thought to be an experimental procedure that has yet to show a clear advantage over conventional chemotherapy in adult recurrent medulloblastoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,[20][21][22] One case report of two patients has shown that high-dose chemotherapy consisting of busulfan and thiotepa followed by infusion of autologous hematopoietic stem cells produced disease-free survival times of 20 and 27 months after bone marrow relapse of medulloblastoma. 15 High-dose carboplatin, thiotepa and etoposide with autologous stem-cell rescue have also shown some activity against recurrent medulloblastoma. 11 High-dose chemotherapy is still thought to be an experimental procedure that has yet to show a clear advantage over conventional chemotherapy in adult recurrent medulloblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…9 Promising results with HDCT/ASCT prompted us to use this form of therapy for young adults with recurrent medulloblastoma, who were otherwise healthy and had no possibility of cure with conventional dose therapy. [10][11][12][13][14][15] Here, we report the outcomes of six adults who underwent HDCT (cyclophosphamide, carboplatin, thiotepa, etoposide) with ASCT for medulloblastoma relapse. Table 1 lists the clinical profile of patients 1-6.…”
mentioning
confidence: 99%
“…Nitrosurea-based protocols did produce impressive responses [26,55], but the pulmonary toxicity was too high [55,56]. The thiotepa/busulfan protocols have also been used successfully in 3 adults with metastatic relapse of medulloblastoma [33,57,58]. Cyclophosphamide appeared to be particularly effective in this group of tumors.…”
Section: Medulloblastomas/pnet (Primitive Neuroectodermal Tumors)mentioning
confidence: 99%
“…High-dose chemotherapy with autologous stem cell support in an adult with bone marrow relapse of medulloblastoma Millot et al 1 recently reported the effectiveness of treatment strategies including chemotherapy with etoposide and carboplatin followed by high-dose chemotherapy with peripheral blood stem cell transplantation in two adults with recurrent extraneuronal medulloblastoma (patients still in complete remission 20 and 27 months after treatment). We describe a case of an adult with medulloblastoma treated with the same regimen for bone and bone marrow metastasis involvement.…”
mentioning
confidence: 99%